Multikulturalisme Pada Masa Dinasti Abbasiyah - Nabila Widya; Meyniar Albina (CV. ITTC INDONESIA, 2024)
This article was written to analyze the history of multiculturalism during the Abbasid Dynasty. While writing this article, the author used a library research method with a descriptive analysis approach. Reference sources were obtained from various printed books, digital books, and articles related to multiculturalism during the Abbasid Dynasty. These sources were processed into new information related to the main topic of discussion. With this research, several results were found, including (1) there was a social status in social life at the Abbasid Dynasty, (2) the existence of an immigrant religion that is Buddhism, (3) a political system similar to the Persian nation and a government system that emphasized the Khalifah came from the Arab nation, (4) the existence of international trade in the city of Baghdad which became a transit center for trade.